Power-centric design of high-speed I/Os - Hatamkhani, Hamid; Lambrecht, Frank; Stojanovic, Vladimir; Yang, Chih-Kong Ken (2006 43rd ACM/IEEE Design Automation Conference, 2006)
With increasing aggregate off-chip bandwidths exceeding terabits/second (Tb/s), the power dissipation is a serious design consideration. Additionally, design of I/O links is constrained by a complex set of specifications such as voltage levels, voltage noise, signal deterministic jitter, random jitter, slew rate, BER etc. These specifications lead to complex tradeoffs for both circuits and circuit architecture in order to minimize power. This paper presents a design framework that enables the analysis of tradeoffs in the design of an I/O transmitter. The design framework includes BER analysis with a channel model coupled with logic sizing optimization that is constrained by the desired signaling specification.